Optimization Of Reflecting Online Listening Comprehension Through SelfDirected Learning On English Proficiency For Teacher - Astuti, Dwi; Drivoka Sulistyaningrum, Siti (International Journal of Educational Research & Social Sciences, 2023)
This study aims to: (1) evaluate students' C1 hearing comprehension challenges; (2) examine students' C1 listening comprehension improvement techniques; and (3) track students' C1 listening comprehension through self-directed learning. Five students from the State University of Jakarta's Magister degree in English Language Education participated in this study, which used a case study methodology. The study involved watching the weekly data report for written self-reflection. The results show that the majority of pupils struggle with filling gaps in C1 Listening. Most of them got difficulties in determining detailed information, mishearing, and because of speaking fast of the speaker. From the results, it is also clear that the students employed note-taking, focus, and attention skills as well as metacognitive strategies to address the challenges they experienced. As part of their self-directed learning in listening comprehension, the students can consider what they have learned or experienced, develop, and define their methods for gathering and assimilation new information.